Self-application of aminoglycoside-based creams to treat cutaneous leishmaniasis in travelers. - Oussama Mouri; Cléa Melenotte; Romain Guéry; Camille Cotteret; Arnaud Schweitzer-Chaput; Alice Perignon; Marc Thellier; Emmanuelle Bourrat; Florentia Kaguelidou; Jean Yves Siriez; Denis Malvy; Jean-Pierre Gangneux; et al. (Public Library of Science (PLoS), 2023)
Background In endemic foci, the use of an aquaphilic cream containing paromomycin with/without gentamicin to treat cutaneous leishmaniasis (CL) is safe, painless and cures 78-82% of patients with New and Old World CL. Self-application in travelers requires evaluation. Methods Travelers with 1-10 lesions of confirmed CL were prospectively treated with the paromomycin-gentamicin formulation (WR279396, 2012-2017, Group 1) and carefully follow up, or treated with a locally produced paromomycin-only cream (2018-2022, Group 2). The cream was applied once under supervision, then self-applied daily for 20-30 days. A cured lesion was defined as 100% re-epithelialization at day 42 without relapse at three months. Results Medical features were similar in Group 1 (17 patients), and Group 2 (23 patients). Patients were infected with either Leishmania major, L. infantum, L. killicki, L. guyanensis, L. braziliensis, or L. naiffi. Intention-to-treat and per-protocol cure rates were 82% (95% confidence interval (CI) [64.23;100.00]) and 87% (95% CI [71,29;100.00]) in Group 1, and 69% (95% CI [50.76; 88.37]) and 76% (95% CI [57.97; 94.41]) in Group 2. In the pooled Group 1&2, 75% (95% CI [61.58;88.42]) (30/40) and 81% (95% CI [68,46;93.6]) (30/37) of patients were cured in intention-to-treat and per-protocol, respectively. There were no significant differences observed in the success rates between Old World and New World CL (83.3% vs. 60%, p = 0.14). Prospective observations in Group 1 showed that adverse events were mainly pruritus (24%) and pain (18%) on lesions (all mild or moderate). No mucosal involvement was observed in either group. Discussion In this representative population of travelers who acquired CL either in the Old or New World, the 81% per-protocol cure rate of a self-applied aminoglycoside cream was similar to that observed in clinical trials.